Comparison of growth and slaughter performance of Boran and Friesian X Boran cattle under Kenya range conditions - Tonn, R. (1973)
Presents results of field trials carried out to compare growth and slaughter performance of Boran and Friesian x Boran cattle under Kenyan grazing conditions. Data on carcass quality and live weight changes included.